Personal or planetary health? Direct, spillover and carryover effects of non-monetary benefits of vegetarian behaviour. (December 2021) - Shreedhar, Ganga; Galizzi, Matteo M.
Abstract: There is a debate about whether framing motivations as personal or planetary benefits - or both - is more effective at encouraging sustainable actions and promoting positive behavioural spillovers. In a pre-registered online longitudinal experiment, we randomly allocate n = 1242 respondents to either a control condition, or to one of three novel, interactive implementation intention interventions framing the benefits of a vegetarian diet in terms of either personal health, or planetary health, or both personal and planetary health. We ask respondents to choose between real vegetarian or non-vegetarian foods. We then ask them to donate part of their money to a charity. We finally measure their food choices three days and two months after the interventions. Compared to the control group, we find that participants assigned to any of the behavioural interventions are twice as likely to choose a vegetarian option. We find no statistically significant differences in the proportions of vegetarian options across the three experimental conditions. We find evidence of a positive behavioural spillover on the donations to charity amongst participants exposed to combined personal and planetary health. Three days after the interventions, participants allocated to this combined frame still reported to eat more vegetarian meals than in the control group. Such carryover effects, however, did not persist two months after the interventions. Overall, our research offers new insights about framing behavioural interventions to motivate sustainable actions and their potential behavioural spillovers. Highlights: Participants assigned to control, or implementation intention groups framing veg food benefits in personal, planetary, or personal+planetary health terms. They choose whether to have a real veg item, and then to donate. Food choices measured three days and two months later. Participants in all experimental conditions are twice as likely to choose a veg option compared to the control group. The combined personal and planetary health condition induced a positive behavioural spillover on charitable donations. Participants in the combined condition reported eating more veg meals three days after. Carryover effects did not persist two months later.